The Holistic Well-being Concepts in Relation to Quality of Life - Jiwattanasuk, Narumon; Pannavoravat, Phrakrupalad; Sirikanchana, Pataraporn (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
These days more people search for better physical and mental health conditions. Everyone strives for the well-being, especially during this uncertainty due to the Covid-19 pandemic. Therefore, well-being has become an interesting topic nowadays. This study presents the critical review of holistic well-being concepts and how the concepts related to the quality of life. The study explores the definition of well-being in terms of Western, Eastern, and Buddhism concepts. To illustrate, the Western concept presents two aspects: subjective well-being and psychological well-being. Meanwhile, the Eastern concept explains the definition of well-being from the perspectives of quality of life and Gross National Happiness. The Buddhist principle concept presents well-being regarding four dimensions: physical, moral, emotional, and intellectual. The study then has introduced the concept of holistic well-being which is classified into four perspectives: physical, psychological, behavioral, and intellectual well-being. Apart from this, reviewing of literatures also represent that holistic well-being is associated with quality of life. The person with holistic well-being would gain the individual benefit of physical and mental health. Holistic well-being is also associated with a good social life. The study also presents several organizations that are applied well-being to improve quality of life. The implication of organizations shows that if employees with good well-being are usually more effective, productive and motivated and this will promote sustainable growth for the organization.